Clustered cases of human adenovirus types 4, 7, and 14 infections in US Department of Defense Beneficiaries during the 2018–2019 season. Issue 2 (21st February 2023) - Pollio, Adam R.; Fries, Anthony C.; Yang, Yu; Hughes, Jerry J.; Fung, Christian K.; Conte, Matthew A.; Kuschner, Robert A.; Collins, Natalie D.; Macias, Elizabeth A.; Hang, Jun
Abstract: Human adenoviruses (HAdV) are genetically diverse and can infect a number of tissues with severities varied from mild to fatal. HAdV types 3, 4, 7, 11, 14, 21, and 55 were associated with acute respiratory illnesses outbreaks in the United States and in other countries. The risk of outbreaks can be effectively controlled by HAdV vaccination or mitigated by screening and preventive measures. During the influenza season 2018–2019, the DoD Global Respiratory Pathogen Surveillance Program (DoDGRS) received 24 300 respiratory specimens. HAdV samples that produced positive cytopathic effects in viral cultivation were subjected to next‐generation sequencing for genome sequence assembly, genome typing, whole genome phylogeny, and sequence comparative analyses. A variety of HAdV types were identified in this study, including HAdV types 1–7, 14, 55, and 56. HAdV types 4, 7, and 14 were found in clustered cases in Colorado, Florida, New York, and South Carolina. Comparative sequence analyses of these isolates revealed the emergence of novel genetic mutations despite the stability of adenovirus genomes. Genomic surveillance of HAdV suggested possible undetected outbreaks and shed light on prevalence, genetic divergence, and viral evolution of HAdV. Continued surveillance will inform risk assessment and countermeasures.